Token-based code clone detector for Dart language - Khazaal, Yasir Mohammed; Hammo, Asma’a Y (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Reusing the code in multiple locations is called in software engineering Code Clone. Detection of a clone is important to reduce the maintenance time and size of code. There are four techniques to detect the code clone: text-based, token-based, AST(Abstract Syntax Tree) based, and PDG(Program Dependence Graph) based. In this paper, we propose and implement the token-based method for code clone detection in the Dart language. The proposed method is evaluated by injecting clones to Dart programs. Results show that the proposed method detects all the injected codes.